The Theology of Relevance: Nowhere to Lay Its Head - McIntyre, John (Toronto journal of theology, 2002)
This paper takes this concept of relevance and marries it to christological themes and thereby explores a theology of relevance through which questions of meaning and truth might be addressed. An initial distinction has to be made between primary and secondary relevance. Primary relevance refers to the "given" of the Christian faith and the events from which it sprang. Secondary relevance refers to the application of this givenness to the generations of Christians who followed. In this discussion "relevance" is understood christologically as "intrinsic relatedness."